4th International Conference on child and adolescent psychopathology - Kok Wei, Wee (Pusat Pengajian Sains Kesihatan, 2009)
To assess and compare working memory of children with Attention Deficit Hyperactivity Disorder (ADHD}, their sibling and those children with other chronic medical illness. Method: By using a cross-sectional design, 57 subjects were recruited through universal sampling from Hospital Universiti Sains Malaysia. a) ADHD group (n= 21), b) siblings of ADHD children group {n=15), and c) non-ADHD children with chronic medical condition as the control group (n = 21}. All subjects were aged between 6 and 15 years, and ADHD was diagnosed according to DSM-IV-TR. Those with other psychiatric comorbidity or Intelligence Quotient (IQ) Jess than 70 were excluded. Three tests from the Working Memory Test Battery for Children were used for assessment. Digit Recall was used for assessment of the phonological loop component, Maze Memory test for the visuospatial sketch pad component and Backward Digit Recall for the central executive component. Result: ADHD children and their siblings showed similar impairment and both differed from the control group on the Maze Memory test. ADHD children also showed Impairment in Digit Recall test, however the sibling group did not differ from the control group on this test. The score of Backward Digit Recall did not show any significant difference between the 3 groups. Conclusion : Impairment of the visuospatial sketch pad component of working memory seems to cluster in ADHD children and their siblings. Thus, Impairment of vlsuospatial sketch pad component may point towards an endophenotype of ADHD.